Maximizing Economic Host Capacity Related to Distributed Generation, and Improving the Power System Performance - Reza Eslami; Mahdi Bagheri (AUT Journal of Electrical Engineering, 2023)
There are numbers of technical limitations that must to be satisfied for the operation of the power systems, and these limitations are related to the power flow of the power system, thus the solar panels cannot inject any unlimited amount of power into the power system. Therefore, the maximum injection power of solar panels is limited to the specific value. This issue is also true for the reactive power produced or consumed by SVCs and solar panels, so the maximum injected power of photovoltaic panels must be obtained in such a way that the technical limitations of the power system are maintained. In the current research, a 33 bus radial distribution network has been considered and the goal is to maximize the injection power of photovoltaic panels, minimize the network power losses, by reconfiguring in this type of the network and establishing effective coordination between the control devices, including the output reactive power of photovoltaic panels and the fire angle of the SVC and graph of the power system. The bus voltage should be within the allowed range, and the cost of purchasing electricity from the upstream network should be minimized. The results of the simulation on the 33 bus radial network confirm the validity of the above claims.